Women’ knowledge about breast cancer and colon cancer - Silva, Nancy Capretz Batista da; Franco, Maria Aparecida Paiva; Marques, Susi Lippi (Paidéia (Ribeirão Preto), 2005)
In Brazil, breast cancer and colon cancer incidences are highly related to the lack of information. It is important to evaluate the knowledge that the feminine population has about this matter to establish strategies in order to decrease those events. In this context, the purpose of this study was to evaluate the knowledge that 294 women (hospitals, schools and universities functionaries, teachers and professors), aging from 20 to 57 years old, have about this subject employing an objective test and a questionnaire. Data revealed that although 89.11% of them tried to assume preventive conducts, there are still some doubts about breast and colon cancer incidence and prevention forms. It is supported the instrument (objective test) viability and applicability as a technical resource for a intervention planning that disseminates knowledge about the disease, which might result in a change of the population behavior on prevention and precocious detection of breast ad colon cancer in Public Health area.